(Table 2) Radiocarbon datings of bottom sediments from the Gulf of Riga, Baltic Sea - Vladimir M Kuptsov; Alexander P Lisitzin; Bella B Zel extquotesingledina (PANGAEA, 1982)
Radiocarbon datings have been made on bottom sediments collected in the Gulf of Riga. These age determinations have been made on organic matter, much of which supplied with stream runoff and having some initial ages ranging from 2000 to 6000 yrs (in different rivers). This greatly complicates interpretation of obtained data. Average sedimentation rates, as determined by the equation of linear regression for four sediment cores, vary from 0.2 to 2.0 mm/yr.
Supplement to: Kuptsov, VM et al. (1982): Sedimentation rates in the Gulf of Riga, from radiocarbon data. Oceanology, 22(4), 455-458